Pengembangan Buku Pedoman Praktek Kerja Lapangan (PKL) Untuk Mahasiswa (Universitas Negeri Jakarta, 2019)
The development research is aimed to result a print media of guidebook practice of fieldwork for student in Majoring of Educational Technology. This guidebook can be used to facilitate the student who will implement fieldwork. In developing the guidebook, developers use the model product development presented by Rowntree through three rounds of the main planning; preparation of writing; writing and editing. Evaluation on research development it uses approach formative evaluation modified, consisting of experts review (expert matter and media experts) and field test. The evaluation involving one matter, one media experts and 22 users. Based on process and procedures in developing guidebooks, as well as the trial that has been carried out can be expressed that the guidebook has good quality and can be used to facilitate student Majoring of Educational Technology State University of Jakarta in terms of the fulfillment of information on fieldwork practice.